Nobel laureates in search of identity & integrity : voices of different cultures - Hallengren, Anders, 1950- (World Scientific, 2004)
In this collection of essays, biographies and Nobel lectures, tenNobel Laureates from five continents give various and startlingperspectives on current questions about modernity and tradition, unityand diversity, integration, identity, integrity, gender and sexualroles in a multicultural world of change. It is also a book onself-confidence and presents different ways to self-knowledge andcultural individuality. Published in print for the first time, thesestudies and penetrating observations on topical issues, written byleading authors and intellectuals from many distant countries, make upone o.